عوائــــــق قيــــــام الحكــــــم الراشـــــد في الجزائـــــــر (Revue El-Wahat pour les Recherches et les Etudes, 2015)
Certainly, speaking about the state of orthodox governance in Algeria isn’t reasonable, but the state of few deciders would be actually discussed and disclosed. That’s a state which lacks the institutional framework considered as the most important characteristics of orthodox governance in the developed countries. Thus, the institution of 1996 couldn’t establish some of those characteristics, because of the domination of the president of republic over all of the functional state authorities, on both national and local level. Wherein, he dominates the parliament, the judiciary and the constitutional supervisory institutions leading to confine the fundamental rights and freedoms, especially, the political freedoms. Key words: - Orthodox governance. – President of republic’s Domination. – Judiciary authority. – Parliament. - Constitutional institutions. – Freedom of opinion and expression. – Partisanship freedom.